Clinical and economic feasibility of early diagnosis in children ametropia - E. Yu. Markova; O. V. Kurganova; L. Yu. Bezmel'nitsyna; N. A. Pron'ko; L. V. Venediktova (Российский офтальмологический журнал, 2018)
Anomalies of refraction belong to the most important issues of pediatric ophthalmology. Purpose. To assess the impact of timely detection of ametropia on clinical and economic aspects of its treatment. Material and methods. A retrospective study of the quality of medical eye care of 260 children with refractive errorsor strabismus aged 5 to 7 years consisted in the analysis of primary medical documentation. Results. Timely medical check-ups which detect ametropias in an early age are shown to be a good preventive measure against the onset of amblyopia, binocular vision disorders, or strabismus. Uncorrected refractive errors in children are characterized by high levels of economic and social burden of the disease (the older the age of the detection of refractive errors, the greater the cost of treatment). Conclusions. The best age at which children should be screened for refractive errors must not exceed 1 year, both from the standpoint of clinical effect and cost effectiveness. Mid-term analysis of the budget impact of early detection of refractive error and strabismus shows that such detection may reduce the costs ofthe treatment of complications // Russian Ophthalmological Journal, 2017; 1: 26-30. doi: 10.21516/2072-0076-2017-10-1-26-30.